(untitled) - Sharma, P. D. (Harrow, U.K., 2005)
Contents of the book is: Environment, public health, industry and agriculture. This book attempts to bring all scattered material on applied effects of microorganisms on environment, human health and welfare together in the form of a complete book on environmental microbiology. Besides students, the book would interest those inclined to learn how microbes help maintain the quality of environment and balance of nature.
Các quá trình sinh học và ứng dụng trong kỹ thuật môi trường,Công nghệ sinh học môi trường,Phân tích và đánh giá sinh học nước,Sinh lý và sinh thái vi sinh vật
Keywords: Microbial ecology,Sinh thái vi trùng học